Otimização do gerenciamento de tempo em projetos com restrições de recurso e múltiplos modos de processamento: estudo de caso na construção civil - Monteiro, Polyanna Maurício de Sena Costa (2018)
The efficient sequencing of activities in civil construction projects is a determining factor of success. In this line, the Scheduling Problem in Projects with Restrictions of Resources and Multiple Processing Modes (MRCPSP) aims to determine the shortest possible execution time of the activities, given the execution times, the amount of resources needed and the total resources available. Previous research on the subject has led Artigues et al. (2003) to propose a linear programming model for the RCPSP. The objective of this dissertation is to expand the scope of the model found in the literature, through the addition of new disjunctive constraints to treat the MRCPSP. The research is normative empirical for experiments. Computational tests were carried out in instances of the PSPLIB library, and a practical case study. With the obtained results it can be affirmed that the model is able to find viable solutions to the problem, in a computational time acceptable.